2014
DOI: 10.1038/srep05999
|View full text |Cite
|
Sign up to set email alerts
|

Angle-resolved Photoemission Spectroscopy Study on the Surface States of the Correlated Topological Insulator YbB6

Abstract: YbB6 is recently predicted to be a moderately correlated topological insulator, which provides a playground to explore the interplay between correlation and topological properties. With angle-resolved photoemission spectroscopy, we directly observed almost linearly dispersive bands around the time-reversal invariant momenta and with negligible kz dependence, consistent with odd number of surface states crossing the Fermi level in a Z2 topological insulator. Circular dichroism photoemission spectra suggest th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 43 publications
2
17
0
Order By: Relevance
“…It also implies that understanding phonon dynamics will be critical in elucidating any topological properties of related hexaborides, e.g. YbB 6 , as has recently been suggested [41][42][43].…”
Section: Resultsmentioning
confidence: 99%
“…It also implies that understanding phonon dynamics will be critical in elucidating any topological properties of related hexaborides, e.g. YbB 6 , as has recently been suggested [41][42][43].…”
Section: Resultsmentioning
confidence: 99%
“…GdB 6 is a localized 4f system with a ferromagnetic order at low temperatures [ 19 ]. YbB 6 is a topology Kondo insulator at low temperatures, and is a classical mixed valence narrow band gap semiconductor [ 1 , 20 , 21 ]. Structural studies are also presented in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, YbB 6 is also predicted to be a TKI. Shi and Feng et al [80,81] investigated the surface and bulk gap structures of YbB 6 by angle-resolved photoemission spectroscopy (ARPES). Shi disclosed that the f -orbitals of YbB 6 are fully occupied, and Yb exists in bivalence states, which is different from mixed-valence Sm in SmB 6 .…”
Section: Optoelectronic Propertiesmentioning
confidence: 99%
“…Furthermore, the metallic surface states of YbB 6 are believed to be topological surface states, which are spin-polarized in plane and locked to the crystal momentum. Feng et al [81] directly observed the bands around the time-reversal invariant momenta exhibiting an obvious linearly dispersive relationship. The in-gap states possess the chirality of orbital angular momentum, which is attributed to the chiral spin texture.…”
Section: Optoelectronic Propertiesmentioning
confidence: 99%